2022
DOI: 10.3390/diagnostics12082008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Diagnostic Performance of Ultrasonography and Magnetic Resonance Enterography in the Assessment of Active Bowel Lesions in Patients with Crohn’s Disease: A Systematic Review and Meta-Analysis

Abstract: We aimed to evaluate and compare the diagnostic performances of ultrasonography (US) and magnetic resonance enterography (MRE) in assessing active bowel lesions in patients with Crohn’s disease (CD). Materials and Methods: We searched PubMed and EMBASE for studies in which US and MRE were used to assess active bowel lesions in CD patients. Bivariate random effect meta-analytic methods were used to estimate pooled sensitivity, specificity, and hierarchical summary receiver operating characteristic (HSROC) curve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(135 reference statements)
0
4
0
Order By: Relevance
“…Most patients presented with ileocolic disease (L3). The median HBI was 2 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16), median serum CRP level was 0.5 mg/dL (0.3-13.56), and median FC level was 129.97 μg/g (0-4510.13). The indications for IUS included monitoring of the treatment response (76/127, 59.8%) and appearance of symptoms of active disease (44/127, 34.6%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most patients presented with ileocolic disease (L3). The median HBI was 2 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16), median serum CRP level was 0.5 mg/dL (0.3-13.56), and median FC level was 129.97 μg/g (0-4510.13). The indications for IUS included monitoring of the treatment response (76/127, 59.8%) and appearance of symptoms of active disease (44/127, 34.6%).…”
Section: Resultsmentioning
confidence: 99%
“…7 Relevant meta-analyses have reported similar diagnostic performances of IUS and MRE, which is the current standard imaging method for non-invasive crosssectional disease activity assessment. 8,9 However, research on the ability of IUS for disease activity assessment or its correlation with other diagnostic tools is not sufficient to fully utilize IUS for tight disease monitoring, although it has the potential to be used more diversely.…”
mentioning
confidence: 99%
“…Various tools allow the evaluation of TH including MRE, IUS, and computed tomography (CT) scans. Comparative studies showed that IUS and MRE have comparable accuracy while avoiding the radiation risk associated with CT scans 13,14 . However, there is no evidence comparing the outcomes of patients monitored closely using different tools.…”
mentioning
confidence: 99%
“…Comparative studies showed that IUS and MRE have comparable accuracy while avoiding the radiation risk associated with CT scans. 13 , 14 However, there is no evidence comparing the outcomes of patients monitored closely using different tools. Importantly, IUS could be the most appropriate method for this approach.…”
mentioning
confidence: 99%